Durability of concrete with pozzolanic admixtures and recycled aggregates - Gurdián Currán, Flora Hebe; Garcés Terradillos, Pedro; Zorzoza Gomez, Emilio; Garcia Alcocel, Eva Maria (Revista ALCONPAT, 2021)
Mechanical and durability properties of concrete with a reduced environmental impact have been evaluated. This approach consist of replacing 50% of Portland cement by fly ash (35%) and spent catalytic cracking catalyst (15%), and also substituting a 20% and 100% of natural coarse aggregates by recycled aggregates. The performance of the prepared concrete consisted of mechanical tests, porosity, air permeability and chloride penetration. The obtained results show that the mechanical performance are significantly reduced in concretes with recycled aggregates and the pozzolanic binder, but durability-related properties are only affected by the use of recycled aggregates. Nevertheless, all the tested formulations are suitable for their use as structural concretes.